Skrining Fitokimia dan Aktivitas Antibakteri Fraksi N-Heksan Ekstrak Metanol Daun Kerai Payung (Filicium decipiens) terhadap Staphylococcus epidermidis - Windi Wildani; Reh Malem br Karo; Wardah Fitria Tanjung; Afri Abdiansyah (University Of Darussalam Gontor, 2022)
Kerai Payung (Filicium decipiens) belongs to the Sapindaceae family, which contains several active compounds that can be used as antibacterial. This study aims to determine secondary metabolites contained in the parasol leaf and the antibacterial activity of n-hexane fraction of the parasol leaf against Staphylococcus epidermidis bacteria. Identification of compound components in the n-hexane fraction of Kerai Payung leaves was carried out qualitatively by TLC using a solvent ratio of n-hexane: ethyl acetate (9:1), (8:2) and (7:3). The best separation result was using nhexane:ethyl acetate (7:3) solvent to produce 7 spots visible at 366 nm UV. The antibacterial activity was tested using the disc diffusion method (Kirby and Bauer diffusion). The concentration variations of the n-hexane fraction were 25%, 50%, 75%, 100%, control (+) cifroploxacin and control (-) DMSO (Dimethyl sulfoxide). The results of the antibacterial test against Staphylococcus epidermidis showed that the average value of the largest inhibition zone diameter was obtained at a concentration of 75%, which was 12.77 mm. The concentration groups of 25%, 50%, and 100% were 9.77 mm, 11.42 mm, 10.75 mm, respectively. Meanwhile, the K(+) group, namely Cifrofloxacin, was 31.95 mm.